Analisis Timbal (Pb) dan Cadmium (Cd) pada Jamu Tradisional Produk Teregistrasi BPOM dan Non Teregistrasi BPOM dengan Spektrofotometri Serapam Atom (SSA) - Arneta Hayfa Radanta; Devi Indriyanti; Grace Maria Intan Yulia Dewi; Imelda Cantika Putri; Pracellya Dyah Ayu Pramesthy; Tirza Renitha Grace Modouw; Yaafindra Nanda Arbella; Abdul Rohman Adnan Prabowo (Pusat riset dan Inovasi Nasional, 2026)
Jamu is a traditional medicine still widely consumed by the public, but it has the potential to be contaminated with the heavy metals lead (Pb) and cadmium (Cd), which are toxic and can cause health problems, particularly to the liver and kidneys. Heavy metal contamination can originate from raw materials grown in polluted environments and from processing, storage, and packaging that do not meet quality standards, particularly for products that have not undergone official supervision. This study aims to analyze the content of lead and cadmium metals in registered and unregistered herbal medicine products. The analysis was carried out using the Atomic Absorption Spectrophotometry (AAS) method after sample preparation through wet digestion using strong acid. Six herbal medicine dosage forms were analyzed, namely powder, chopped, pills, capsules, cream, and shake parem. Method validation included tests for linearity, precision, limit of detection, and limit of quantification to ensure the reliability of the analysis results. The results showed that all registered herbal medicine samples met the safety requirements for Pb and Cd. In contrast, several unregistered herbal medicine preparations, especially powder, chopped, and cream, did not meet the safety requirements for Cd, while the Pb levels in all samples met the safety requirements for Pb. These findings indicate that unregistered herbal medicines carry a higher risk of heavy metal contamination. Therefore, strengthening quality control, selecting safe raw materials, and increasing compliance with regulations are necessary to ensure the safety of herbal medicine consumption and protect public health.